EDUCATION IN AWORKPLACE FROM THE PERSPECTIVE OFA LEARNING ORGANIZATION - Tomaszewska-Lipiec, Renata (European Scientific Journal, ESJ, 2014)
Challenges connected with the development of the knowledge based economy make contemporary work places enter the path of changes. The process of globalization and the pace of changes in all the spheres of economy functioning caused that the optimal concept of management is a learning organization concept which is based on education and learning treated as tools enabling creation of unique resources of knowledge. Using this thesis success can be achieved only by such work places which faster than others will adapt to the changes by investing in ‘learning’. It has to be accepted that employees’ education is an essence of the XXIst century organizations and builds a new economy. This concept was an inspiration to start research which aim was to show employee education in contemporary work places from the perspective of a learning organization. The article presents chosen research results concerning mainly employee education at work places